Analisis Kinerja Koneksi Jaringan Switch Ethernet pada Local Area Network (LAN) - Abdul Karim; Andi Achmadi (Ainet : Jurnal Informatika, 2019)
The development of today's telecommunication network is progressing very fast. Various kinds of telecommunication technology facilities continue to be developed so that users can communicate practically, wherever the location of the user the resides. This study aims to find out what processes are running when data packets are sent such as computing and comparing the speed of packet data transmitted (Throughput), packet loss data (Packet Loss), and time delay data transmission from each user used. The method used in this study is to use literature study by taking data in the field with the aim to Calculate the value of Throughput, delay and packet loss of a packet sent by each user in the network Ethernet Switch. From the results of the study obtained Comparison of Througput of each field of work, seen in the financial field has the highest value. While having the lowest Througput value is in the field of news. Comparison of time delay of each field can be in the field of delay news with the fastest time to send data and in the field of finance delay with the longest time in data transmission. The packet loss data analysis of each experiment gets a good average score in each field according to ITU G.114 standard with 0% percentage.